2010
DOI: 10.2147/opth.s6292
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and patient tolerability of travoprost BAK-free solution in patients with open-angle glaucoma and ocular hypertension

Abstract: The medical treatment of glaucoma has evolved significantly over the past several decades. The main driving forces behind this evolution are the safety profiles and efficacy of these medications. Prostaglandin (PG) analogues are shown to be superior to older drugs in both efficacy and tolerability. Though there are much fewer side effects that manifest after using PG analogues, the adherence and compliance to medication regimens are surprisingly lower than expected. A commonly sited reason is the ocular irrita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…In a literature review by Mirza SK et al, the author enumerates that BAK-free travoprost has demonstrated equal efficacy and less ocular surface toxicity than its preserved counterparts. 9 In the above study BAK-free travoprost demonstrated significant decrease in OSDI scores. These findings are in line with results of the study by Henry JC et al, wherein travoprost BAK-free demonstrated improved mean OSDI scores, decreased hyperaemia and equal or better IOP control compared to either latanoprost or bimatoprost.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In a literature review by Mirza SK et al, the author enumerates that BAK-free travoprost has demonstrated equal efficacy and less ocular surface toxicity than its preserved counterparts. 9 In the above study BAK-free travoprost demonstrated significant decrease in OSDI scores. These findings are in line with results of the study by Henry JC et al, wherein travoprost BAK-free demonstrated improved mean OSDI scores, decreased hyperaemia and equal or better IOP control compared to either latanoprost or bimatoprost.…”
Section: Discussionmentioning
confidence: 71%
“…This is in line with the observations made in previous studies. 8,9,18 The findings of this study have important implications for the medical management of patients with glaucoma, because OSD is common among glaucoma patients, and In choosing an IOP-lowering medication for glaucoma or ocular hypertension, both efficacy and tolerability should be considered. Given the far-reaching effects of ocular inflammation in regard to adherence and failure of filtration surgery, this advancement appears to be much needed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years, as increasing attention has been paid to various ocular surface disorders, such as dry eye disease, conjunctivitis, allergies, and other problems that the preservatives contained in ophthalmic solutions may cause to ocular surface homeostasis, there is increasing demand for ophthalmic solutions that contain little or no preservatives [22]. Actually, clinical efficacy and safety profiles of BAK-free prostaglandin analogues have been well-documented, and their reduced ocular side effects have been indicated [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…BAK-free travoprost was compared with latanoprost containing BAK preservative in patients with superficial punctate keratopathy. After replacing latanoprost containing BAK with travoprost containing SofZia, the score for superficial punctate keratopathy decreased significantly three months later 39,40…”
Section: Safety Of Prostaglandin Analogsmentioning
confidence: 99%